Accuracy Improvement of In-line Near-Infrared Spectroscopic Moisture Monitoring in a Fluidized Bed Drying Process - Bogomolov, Andrey; Mannhardt, Joachim; Heinzerling, Oliver (Frontiers in Chemistry, 2018)
Exploratory analysis of a large representative dataset obtained in a fluidized bed drying of a pharmaceutical powder has revealed a significant correlation of the spectral intensity with the granulate humidity in the whole studied range of 1091.8–2106.5 nm. The effect was explained by dependence of the powder refractive properties, and hence light penetration depth, on the water content. This effect exhibited close spectral similarity to the well-known stochastic variation of spectral intensities caused by the process turbulence (the so-called “scatter effect”). Therefore, any traditional scatter-corrective preprocessing incidentally eliminates moisture-correlated variance from the data. To preserve this additional information for a more precise moisture calibration, a time-domain averaging of spectral variables has been suggested. Its application resulted in a distinct improvement of the prediction accuracy, compared to the scatter-corrected data. Further improvement of the model performance was achieved by application of a dynamic focusing strategy when adjusting the model to a drying process stage. The probe fouling was shown to have a minor effect on the prediction accuracy. The study resulted in a considerable reduction of the root mean-square error of in-line moisture monitoring to 0.1%, which is close the reference method reproducibility and significantly better than previously reported results.